What Happens Next? Using the Story Completion Method to Surface the Affects and Materialities of Digital Privacy Dilemmas. (September 2022) - Watson, Ash; Lupton, Deborah
People's ideas and practices concerning their personal data and digital privacy have received growing attention in social inquiry. In this article, we discuss findings from a study that adopted the story completion method together with a theoretical perspective building on feminist materialism to explore how people make sense of and respond to digital privacy dilemmas. The Digital Privacy Story Completion Project presented participants with a set of four story prompts ('stems') for them to complete. Each introduced a fictional character facing a privacy dilemma related to personal data generated from their online interactions or app use. Our analysis surfaces how privacy is imagined as simultaneously personal and social, redolent with affective intensities, and framed through relational connections of human and nonhuman agents. While the story stems involved scenarios using digital technologies, participants' stories extended beyond the technological. These stories offer insight into why and how the potential for and meaning of digital privacy unfolds into more-than-digital worlds.